2018
DOI: 10.3390/app8050756
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Process and Design Variables in Improving the Performance of Heat Exchanger Tube Expansion

Abstract: Abstract:In the expansion process of a fin-tube heat exchanger, the process variables and shape of the expansion ball affect the deformation of the tube's inner grooves, the adhesion, and the expansion force. These factors influence the efficiency of heat transfer and the lifetime of the expansion equipment. Therefore, this study analyzed the influential variables of the tube expansion process as well as the expansion ball design through experiments and simulations. A new method was proposed to determine the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…With the results obtained using the DEA model of Super Efficiency oriented to inputs with non-decreasing returns to scale, the same conclusions were obtained as those obtained through Statistical Process Control and DOE, so that the order of preference of the die-nozzle models is as follows: 3DND, 1DNL, 2DNV, 4DNK, and 5DNS [32,33]. The methods to optimize the design proposed in [1] were very useful for following work in the improvement of tooling and manufacturing processes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…With the results obtained using the DEA model of Super Efficiency oriented to inputs with non-decreasing returns to scale, the same conclusions were obtained as those obtained through Statistical Process Control and DOE, so that the order of preference of the die-nozzle models is as follows: 3DND, 1DNL, 2DNV, 4DNK, and 5DNS [32,33]. The methods to optimize the design proposed in [1] were very useful for following work in the improvement of tooling and manufacturing processes.…”
Section: Discussionsupporting
confidence: 62%
“…Table 5 presents ANOVA duration vs. die-nozzle model. Table 6 presents the the results of the ANOVA for the three variables: duration, volume of production, and volume of scrap, it can be seen that the value P test is limited to a precision of only 1 thousandth, so any value less than this amount is presented as 0.000 [32]. In this case, it can be observed that there is a significant difference in the average duration of at least two die-nozzle models, with a value of significance α = 0.05 [33].…”
Section: Results 23-awg Production Processmentioning
confidence: 99%
“…In Gouveia et al, 31 the formability of aluminium tubes and the effects of the process parameters using numerical simulations were investigated. The numerical models were also used to study the effects of several configurations (expansion method, alloy, pipe loading) on the mechanical properties of the steel subjected to tubular expansion, as proposed by Mack, 32 or to investigate the effect of the process parameters, as proposed by Avalle et al 2,33 and Han et al, 34 who used the expansion force rate to define the amount of adhesion in the tube’s inner grooves.…”
Section: Introductionmentioning
confidence: 99%